Trends in the prevalence of antenatal and postnatal depression in Bangladesh: A systematic review and meta-analysis - Mohammad Injamul Hoq; Md Mohotasin Hossain; Mohammad Aktar Sayeed; Md Jakaria (Heliyon)
Background: Maternal depression negatively impacts the health of both mothers and their children. Although several studies have reported on the prevalence of antenatal depression (AND) and postnatal depression (PND) in Bangladesh, reliable estimates based on meta-analysis have yet to be established. This study aims to determine the prevalence of “AND” and “PND” among Bangladeshi mothers, as well as the prevalence of “PND” during various phases of a child's development, while also identifying the associated factors for both “AND” and “PND”. Methods: We conducted a systematic search in PubMed, Scopus, Cochrane, and a national database called Bangla Jol for studies published from the year 2000 until December 31, 2020. From 163 screened studies, eighteen eligible studies on the prevalence of “AND” and “PND” were included for meta-analysis. A random-effects model was used for this analysis. We also performed subgroup analyses considering “PND” at different stages, study quality, and prevalence based on the decade of publication. Results: The pooled prevalence rates were found to be 19.5 % for “AND” (95 % CI: 7.7 %–31.28 %, I2: 98.09 %) and 27.75 % for “PND” (95 % CI: 22.38 %–33.16 %, I2: 97.67 %). In the 2000s, the pooled prevalence was 22.78 % (95 % CI: 17.82 %–27.73 %, I2: 96.65 %). However, there was a significant increase in the prevalence of “PND” in the 2010s, which reached 36.00 % (95 % CI: 23.94 %–48.06 %, I2: 95.76 %). The pooled prevalence at an early stage of the child's development was 17.12 %; during exclusive breastfeeding, it was 25.73 %, and during complementary feeding, it peaked at 48.11 %. Factors associated with maternal depression included unplanned pregnancies, various forms of intimate partner violence (including physical, emotional, and sexual violence), a preference for male children, and strained relationships with husbands and mothers-in-law. Conclusion: A rising trend in the prevalence of maternal depression has been observed in Bangladesh. Health policymakers need to prioritize addressing maternal depression. The data indicates that the prevalence of postpartum depression was higher in the 2010s compared to the previous decade. It is crucial to raise awareness among mothers about the importance of screening for depression during the perinatal period, and to integrate such screenings into family planning and mental health services.